A new model for solving fuzzy linear fractional programming problem with ranking function - Sapan Kumar Das; Tarni Mandal (Journal of Applied Research on Industrial Engineering, 2017)
In this paper, we studied fuzzy linear fractional programming (FLFP) problems with trapezoidal fuzzy numbers where the objective functions are fuzzy numbers and the constraints are real numbers. In this study, in order to obtain the fuzzy optimal solution with unrestricted variables and parameters, a new efficient method for FLFP problem has been proposed. These proposed methods are based on crisp linear fractional programming and newly transformation technique is also used. A computational procedure has been presented to obtain an optimal solution. To show the efficiency of our proposed method a real life example has been illustrated.